Eksistensi Anak Perempuan dalam Hukum Kewarisan Syiah - Rama, Faby Toriqir (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2019)
This is a bibliographical research that discusses the justice of girls in Shi’ah inheritance system. The issue which is the subject of discussion is the position of female heirs, especially girls, who in Sunni inheritance system is not treated equally with other heirs, whether they are equal or not. Because in the Sunni inheritance system, male superiority is highly exalted. Between sons and daughters, even though they are equal in the eyes of the heir, still have an unbalanced power in veiling other heirs. Whereas in Shi’ah inheritance system, girls are positioned as equals to boys. They have the same hijab power. In addition, Presidential Instruction No. 1 of 1991 concerning Compilation of Islamic Law (KHI) also applies the principle of equality between girls and boys in terms of veiling other heirs. Nevertheless, KHI did not adopt the class system directly. However, it is explicitly stated in article 181 and article 182 that the existence of a daughter causes sibling, sibling with the same mothe or sibling with the same father does not receive part of the inheritance. [Artikel ini adalah hasil penelitian pustaka yang membahas keadilan anak perempuan di dalam hukum kewarisan Syiah. Permasalahan yang menjadi pokok bahasan adalah posisi ahli waris wanita—terutama anak perempuan—yang di dalam hukum kewarisan Sunni tidak diperlakukan setara dengan ahli waris lainnya, baik yang sederajat atau tidak. Sebab di dalam hukum kewarisan Sunni, superioritas laki-laki sangat diagungkan. Antara anak laki-laki dan anak perempuan—walaupun sederajat di mata pewaris—tetap memiliki kekuatan yang tidak seimbang di dalam menghijab ahli waris yang lain. Sedangkan di dalam hukum kewarisan Syiah, anak perempuan diposisikan setara dengan anak laki-laki. Mereka memiliki kekuatan menghijab yang sama kuatnya. Selain itu, Inpres No. 1 Tahun 1991 tentang Kompilasi hukum Islam (KHI) juga menerapkan prinsip kesetaraan antara anak perempuan dengan anak lakilaki dalam hal menghijab ahli waris lainnya. Kendati demikian, KHI tidak mengadopsi sistem Kelas secara langsung. Namun, secara eksplisit tersebut di dalam pasal 181 dan pasal 182 bahwa eksistensi anak perempuan menyebabkan saudara kandung, saudara seibu, atau saudara seayah tidak menerima bagian harta waris.]